STRATEGI PENGEMBANGAN INDUSTRI KECIL TAHU DI KABUPATEN TEGAL - Mubaranto, Hendra; Baga, Lukman M.; Sarma, Ma’mun (Jurnal Manajemen Pembangunan Daerah, 2016)
The purposes of this study are to analyze the business performance and the ability of the tofu industry to become economic base, analyze the factors that affect the performance, and formulate strategies for the development of tofu small scale industry. The data of this study was collected through field survey, in-depth interviews with related experts, questionnaire technique and study documents. The data was analyized using the business feasibility, Hayami added value, regression, LQ, IFE and EFE, and SWOT. The business feasibility analysis of the tofu small scale industry has met all requirements. The production inputs and labour are significantly influence for the performance of tofu small scale industry. The tofu small scale industry becomes an economic base commodity in Adiwerna, Pangkah, and Tarub Subdistricts. Strategies on the development of tofu small scale industry in Tegal District among others are improving: the image of tofu to the higher level of consumer by packaging and brand design, the regional branding, the market penetration of the supply chain and control of soybean prices, and using alternative tofu raw material, optimizing the economic value of waste.Keywords: Development strategy, process food industry, Tegal District, small scale industry ABSTRAK Tujuan penelitian adalah menganalisis kinerja usaha dan kemampuan industri kecil tahu menjadi basis ekonomi, menganalisis faktor-faktor yang mempengaruhi kinerja dan merumuskan strategi pengembangan industri kecil tahu. Data penelitian ini dikumpulkan melalui survei lapangan, wawancara mendalam dengan pakar, kuesioner dan studi dokumen. Teknik pengolahan data menggunakan analisis kelayakan usaha, nilai tambah Hayami, regresi, LQ, IFE dan EFE, dan SWOT. Analisa kelayakan usaha industri kecil tahu telah memenuhi semua persyaratan. Input produksi dan tenaga kerja merupakan faktor-faktor yang mempengaruhi kinerja industri kecil tahu. Industri kecil tahu mampu menjadi komoditas basis ekonomi di Kecamatan Adiwerna, Kecamatan Pangkah dan Kecamatan Tarub. Alternatif strategi pengembangan industri kecil tahu di Kabupaten Tegal antara lain adalah meningkatkan: citra produk guna membidik kelas konsumen yang lebih tinggi melalui desain kemasan dan merek, regional branding, penetrasi terhadap rantai suplai dan pengendalian harga kedelai, dan memanfaatkan bahan baku tahu alternatif, optimalisasi nilai ekonomi limbah industri tahu.Kata kunci : Industri kecil, industri makanan olahan, Kabupaten Tegal, strategi pengembangan